2021
DOI: 10.2166/ws.2021.342
|View full text |Cite
|
Sign up to set email alerts
|

Smart water grid: a review and a suggestion for water quality monitoring

Abstract: Water is a valuable resource and an elixir of life. It is intimately linked to the living standards around the world. Reducing the water stress and conserving the resource is vital. It is the need of the hour to ameliorate the conventional water resources systems to monitor the water quantity and quality parameters continuously in real-time. Smart solutions play an important role in monitoring the system parameters and make on-site measurements. This paper focuses on Smart Water Grid, an ingenious way to monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…It is intended to provide some details regarding the possible applications, the sensors exploited, and the characteristics of the wireless communication channel. More exhaustive reviews on such topics can be found in the literature [2,4,6,[28][29][30][31].…”
Section: Review Of Swg Based On Standard Radio Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is intended to provide some details regarding the possible applications, the sensors exploited, and the characteristics of the wireless communication channel. More exhaustive reviews on such topics can be found in the literature [2,4,6,[28][29][30][31].…”
Section: Review Of Swg Based On Standard Radio Communicationmentioning
confidence: 99%
“…As was presented in the previous Sect., SWGs deal with the management of water distribution networks [1]. As far as the communication network of such SWGs is concerned, it results from previous reviews [2][3][4][5] that the vast majority of the cases employ radio wave communication for information transfer between sensor nodes of the network. However, the review [1], among the various wireless techniques, also considered acoustic wave-based communication as a possible way to transfer information, since it is effectively a wireless communication technique.…”
Section: Acoustic Based Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid advancements of diverse and complementary electronic technologies such as long-range, low-power radio protocols, low-power microcontrollers, and sensors, along with energy harvesting solutions, have been enabling a pervasive diffusion of the Internet of Things (IoT) [ 1 , 2 ]. Since water plays a crucial role for life on the planet, the application of IoT technologies to improve the management of water for both drinking [ 3 , 4 , 5 ] and irrigation [ 6 ] use is compelling. One of the main limitations to a large-scale diffusion of sensing nodes for wireless monitoring of water distribution infrastructures is the cost of the individual nodes in the grid.…”
Section: Introductionmentioning
confidence: 99%
“…Other actions are based on the digital metering of water consumption, which could allow the detection of leaks at the user level and distribution network level [11]. Likewise, the monitoring and measurement of system parameters (e.g., pressure and water flow) improve decision-making and optimize the resources of water utilities and authorities [12], thus minimizing water leakage in their networks [13,14].…”
Section: Introductionmentioning
confidence: 99%